Structure/Function Studies of the α4 Subunit Reveal Evolutionary Loss of a GlyR Subtype Involved in Startle and Escape Responses - Leacock, Sophie; Syed, Parnayan; James, Victoria M.; Bode, Anna; Kawakami, Koichi; Keramidas, Angelo; Suster, Maximiliano; Lynch, Joseph W.; Harvey, Robert J. (Frontiers in Molecular Neuroscience, 2018)
Inhibitory glycine receptors (GlyRs) are pentameric ligand-gated anion channels with major roles in startle disease/hyperekplexia (GlyR α1), cortical neuronal migration/autism spectrum disorder (GlyR α2), and inflammatory pain sensitization/rhythmic breathing (GlyR α3). However, the role of the GlyR α4 subunit has remained enigmatic, because the corresponding human gene (GLRA4) is thought to be a pseudogene due to an in-frame stop codon at position 390 within the fourth membrane-spanning domain (M4). Despite this, a recent genetic study has implicated GLRA4 in intellectual disability, behavioural problems and craniofacial anomalies. Analysing data from sequenced genomes, we found that GlyR α4 subunit genes are predicted to be intact and functional in the majority of vertebrate species - with the exception of humans. Cloning of human GlyR α4 cDNAs excluded alternative splicing and RNA editing as mechanisms for restoring a full-length GlyR α4 subunit. Moreover, artificial restoration of the missing conserved arginine (R390) in the human cDNA was not sufficient to restore GlyR α4 function. Further bioinformatic and mutagenesis analysis revealed an additional damaging substitution at K59 that ablates human GlyR α4 function, which is not present in other vertebrate GlyR α4 sequences. The substitutions K59 and X390 were also present in the genome of an ancient Denisovan individual, indicating that GLRA4 has been a pseudogene for at least 30,000-50,000 years. In artificial synapses, we found that both mouse and gorilla α4β GlyRs mediate synaptic currents with unusually slow decay kinetics. Lastly, to gain insights into the biological role of GlyR α4 function, we studied the duplicated genes glra4a and glra4b in zebrafish. While glra4b expression is restricted to the retina, using a novel tol2-GAL4FF gene trap line (SAIGFF16B), we found that the zebrafish GlyR α4a subunit gene (glra4a) is strongly expressed in spinal cord and hindbrain commissural neurones. Using gene knockdown and a dominant-negative GlyR α4aR278Q mutant, we found that GlyR α4a contributes to touch-evoked escape behaviours in zebrafish. Thus, although GlyR α4 is unlikely to be involved in human startle responses or disease states, this subtype may contribute to escape behaviours in other organisms.